Информационно-программная поддержка курса «Алгоритмы и программное обеспечение систем коммутации» - Королев, В. Н. (УАДО, 2002)
The informational and programming support of the subject “Algorithms and software of switched systems” for speciality “Informational network of communication” is considering. It include: 1) the electronic variant of this subject summary; 2) the Web site with this subject contents; 3) the system for modeling the automatic and digital telephone exchanges functionality; 4) the system for studying the software of switch units on Assembler level.
Keywords: обеспечение систем коммутации»